Use and abuse of the concept of resilience - Schiera, Adriana (2005)
The resiliencia is a concept that helps to understand situations in which certain persons overcome the adversity. Premise that allows to go deeply into his content and limits to deal with his royal dimension, certain human characteristics, with the frame of the Psychology and the human sciences.  Present I articulate it he, covers the psychological relations that are established on having approached this subject matter.